Update on the Molecular Genetics of Timothy Syndrome - Bauer, Rosemary; Timothy, Katherine W.; Golden, Andy (Frontiers in Pediatrics, 2021)
Timothy Syndrome (TS) (OMIM #601005) is a rare autosomal dominant syndrome caused by variants in CACNA1C, which encodes the 1C subunit of the voltage-gated calcium channel Cav1.2. TS is classically caused by only a few different genetic changes and characterized by prolonged QT interval, syndactyly, and neurodevelopmental delay; however, the number of identified TS-causing variants is growing, and the resulting symptom profiles are incredibly complex and variable. Here, we aim to review the genetic and clinical findings of all published case reports of TS to date. We discuss multiple possible mechanisms for the variability seen in clinical features across these cases, including mosaicism, genetic background, isoform complexity of CACNA1C and differential expression of transcripts, and biophysical changes in mutant CACNA1C channels. Finally, we propose future research directions such as variant validation, in vivo modeling, and natural history characterization.